Integration Environmental Aspects onto Customer Requirement to Develop Green Quality Function Deployment - Abdul Wahid, Maryam; Dawood, Lamyaa (Anbar Journal of Engineering Sciences, 2023)
The extensive global competition between companies and the development of new industrial technologies have greatly contributed to the current competitive conditions Like industrial companies, customers demand high quality products, low prices and better performance. This fierce competition has led to concerns about improved product design. This development is based on GQFD. Model of this developed Water pump is employed by CAD solid model (version 7). In order to achieve competition and high quality and high performance in the Iraqi market. GQFD demonstrates the balance between product development and environmental protection. Used a water pump for a home air cooler as a case study. Data is collected and distributed using personal interview methods and questionnaire forms to indicate customer requirements. The data is then analyzed using Pareto chart and AHP to prioritize customer needs. These priorities are then placed in house of quality and matrix of relationships between customer requirements and technical characteristics is established. The product has been developed from electrical to mechanical, in addition to using accumulated, stored and recycled materials; it also saves 20% of energy, thereby combining energy reduction with the use of damaged materials and their re-entry into work. As a result, the cost of pump manufacturing will decrease